Tamarindus indica Extract Alters Release of Alpha Enolase, Apolipoprotein A-I, Transthyretin and Rab GDP Dissociation Inhibitor Beta from HepG2 Cells - Chong, Ursula Rho Wan; Abdul-Rahman, Puteri Shafinaz; Abdul-Aziz, Azlina; Hashim, Onn Haji; Junit, Sarni Mat (Public Library of Science, 2012)
Background: The plasma cholesterol and triacylglycerol lowering effects of Tamarindus indica extract have been previously described. We have also shown that the methanol extract of T. indica fruit pulp altered the expression of lipid-associated genes including ABCG5 and APOAI in HepG2 cells. In the present study, effects of the same extract on the release of proteins from the cells were investigated using the proteomics approach. Methodology/Principal Findings: When culture media of HepG2 cells grown in the absence and presence of the methanol extract of T. indica fruit pulp were subjected to 2-dimensional gel electrophoresis, the expression of seven proteins was found to be significantly different (p<0.03125). Five of the spots were subsequently identified as alpha enolase (ENO1), transthyretin (TTR), apolipoprotein A-I (ApoA-I; two isoforms), and rab GDP dissociation inhibitor beta (GDI-2). A functional network of lipid metabolism, molecular transport and small molecule biochemistry that interconnects the three latter proteins with the interactomes was identified using the Ingenuity Pathways Analysis software. Conclusion/Significance: The methanol extract of T. indica fruit pulp altered the release of ENO1, ApoA-I, TTR and GDI-2 from HepG2 cells. Our results provide support on the effect of T. indica extract on cellular lipid metabolism, particularly that of cholesterol.